2019
DOI: 10.1088/1742-6596/1388/1/012047
|View full text |Cite
|
Sign up to set email alerts
|

Multiple intelligences and academic performance in basic education students: An analysis of main components

Abstract: This research included a sample of students aged between 8 and 16 years, residents of San José de Cúcuta city, Colombia, belonging to socio-economic strata 1 and 2. Multiple intelligences (musical, logical-mathematical, interpersonal, naturalistic, intrapersonal, kinesthetic, linguistic and spatial) were measured according to the proposal by Gardner and school performance as an average of each subject taken during the first two cuts of the school year. The authors applied a principal components analysis with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…When measured against the mean, male students have a naturalist intelligence of 6.1930, whereas female students have a naturalist intelligence of 6.7313. Similar conditions were confirmed by the findings of a study of students aged 8-16 years, which found that girls have higher naturalistic intelligence ratings (Hernández, Prada, and Rincón 2019).…”
Section: Discussionsupporting
confidence: 74%
“…When measured against the mean, male students have a naturalist intelligence of 6.1930, whereas female students have a naturalist intelligence of 6.7313. Similar conditions were confirmed by the findings of a study of students aged 8-16 years, which found that girls have higher naturalistic intelligence ratings (Hernández, Prada, and Rincón 2019).…”
Section: Discussionsupporting
confidence: 74%
“…In line with this, nurse educators also try their best to create learning opportunities that are interactive and applicable to the requirements of their students (Amerson, 2006). However, students' academic performance depends on multiple intelligence and learning styles (Hernandez Suarez et al, 2019).…”
Section: Addressing Multiple Intelligences and Learning Stylesmentioning
confidence: 99%
“…Numerous studies have looked at and demonstrated a link between students' multiple intelligence and emotional intelligence and their academic achievement, notably in English (Ayesha & Khurshid, 2013;Babantunde & Ayoola, 2020;Chew et al, 2013;Hernandez, 2019;Meher, 2021;Novelo, 2019;Yahaya et al, 2012). Naderi et al (2012) contended that, principally in support of multiple intelligence, some psychologists observed a connection between academic success and multiple intelligence and claimed a cause-and-effect relationship between the two variables.…”
Section: Introductionmentioning
confidence: 99%